Burkina Faso : Staff Assessment of Qualification for the Multilateral Debt Relief Initiative. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Burkina Faso reached the completion point under the enhanced HIPC Initiative on April 12, 2002. Staff is of the view that all criteria have been met and recommends that the Board determine that Burkina Faso qualifies for immediate debt relief under the MDRI.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Burkina Faso